2016
DOI: 10.1039/c6nr00712k
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical organization and molecular diffusion in gold nanorod/silica supercrystal nanocomposites

Abstract: The internal organization of gold nanorod supercrystals is fully described as well as infiltration with silica and SERS performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
61
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 38 publications
(61 citation statements)
references
References 54 publications
0
61
0
Order By: Relevance
“…were fabricated and tested as versatile SERS substrates [12][13][14][15][16][17][18][19][20][21][22][23] . Specifically, porous materials, nanostructures and nanoparticles, routinely reaching uniform SERS enhancement sufficient to overcome single-molecule detection limit independently on excitation/detection conditions, are of growing interest [24][25][26] .…”
mentioning
confidence: 99%
“…were fabricated and tested as versatile SERS substrates [12][13][14][15][16][17][18][19][20][21][22][23] . Specifically, porous materials, nanostructures and nanoparticles, routinely reaching uniform SERS enhancement sufficient to overcome single-molecule detection limit independently on excitation/detection conditions, are of growing interest [24][25][26] .…”
mentioning
confidence: 99%
“…Interestingly, the mesoporous nature of the films can also be used to direct anisotropic nanoparticle growth within the films, and more importantly, that the mesoporous films act as molecular sieves to let small molecules such as quorum sensing signals pass through the film, while larger biomolecules such as proteins are unable to enter [65]. One promising approach for biological studies of bacterial growth on topographically patterned substrates has been reported by Hamon and coworkers, using sol-gel silica growth on gold nanorod supercrystal micropatterns (Figure 5e) [66]. Silica deposition results in a mesoporous thin film throughout the sample, covering the outer part but also forming silica layers between lamellae of ordered gold nanorods which allows molecular diffusion deep into the plasmonic structure, thereby further enhancing the Raman signal and decreasing the detection limit [54].…”
Section: Concept: Sers Detection Of Quorum Sensing For Early Stage Momentioning
confidence: 99%
“…(e) Micropatterned gold nanorod supercrystal arrays coated in mesoporous SiO 2 ; the bottom image shows a cross-sectional view. Image reproduced with permission from RSC publishing [66]. (f) Linear arrays of gold nanoparticles formed through PDMS wrinkling and transfer onto a substrate, reproduced with permission from ACS Publications [62].…”
Section: Concept: Sers Detection Of Quorum Sensing For Early Stage Momentioning
confidence: 99%
“…[29,42] This encapsulation approach, however, has not been successfully applied for GNR superlattices yet. [43] While the GNR superlattice made by the impregnation method was quite stable in water, it became significantly degraded at 150 °C because silica layer was formed over the superlattice and between the individual lamellae of GNRs inside the structure without covering the individual GNRs. [43] While the GNR superlattice made by the impregnation method was quite stable in water, it became significantly degraded at 150 °C because silica layer was formed over the superlattice and between the individual lamellae of GNRs inside the structure without covering the individual GNRs.…”
mentioning
confidence: 99%
“…Recently, an impregnation method has been used to protect the GNR superlattices with porous silica, in which a preformed GNR superlattice on substrate was immersed in a silica precursor solution. [43] To achieve the stability of GNR superlattice at high temperature, therefore, a new method to protect individual GNRs in the superlattice should be developed.In this study, we developed a new method to fabricate 2D hexagonal GNR superlattices on substrate in which each GNR is individually encapsulated with silica, providing an excellent stability at high temperature and in solvents of different polarities. [43] To achieve the stability of GNR superlattice at high temperature, therefore, a new method to protect individual GNRs in the superlattice should be developed.…”
mentioning
confidence: 99%